PEMODELAN PERSAMAAN STRUKTURAL PEMAHAMAN KONSEPTUAL MATEMATIS MATERI ALJABAR, FUNGSI DAN GARIS LURUS PADA SISWA SEKOLAH MENENGAH PERTAMA - Maulidan Kelana; Edy Tandililing; Agung Hartoyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the analysis process and detect the relationship between amathematical conceptual understanding of Algebra, Functions, and Straight Lines withStructural Equation Modeling (SEM). This research is Research and Development(R&D) and Applied Research (AR), wherein this research development, correlation,and experimentation are carried out. The mathematical conceptual understanding testwas developed through the formative research stage, which is preliminary; thepreparation, and design phase, then followed by the formative evaluation; one-to-one,expert review, small group, and field tests. The tests carried out on the test items showa significant level of validity and there are some data that have high levels of outliers,so that must be removed. At the Goodness-of-Fit stage, there are several indicators thatmust be issued because they have a low level of feasibility informing the model. Theresults of the analysis in the study indicate that not all indicators of mathematicalconceptual understanding of each subject have feasibility in the structural model. Theresults of SEM, it is known that there is a significant relationship between amathematical conceptual understanding of Algebra learning subject and the subjectafterward (the Functions and Straight Lines).Keywords: Algebra, Applied Research (AR), Conceptual Understanding Test,Formative Research, Functions, Straight Lines, Structural EquationModeling (SEM), Research and Development (R&D).